Pesticides Residues in Fresh Food of Plant Origin: Case Study in Indonesia - Agung Hendriadi; Sulistiyorini Sulistiyorini; Miranti Reine Devilana (AGRIVITA, Journal of Agricultural Science, 2021)
The use of pesticides in fresh food of plant origin (FFPO) such as horticulture products is widely known. Such broad implementation of pesticide can result in a tremendous usage of pesticides and, afterward, in intolerable levels of pesticide residues in the products. In this work, we analyzed the pesticide residues in FFPO - which include fruits, vegetables, and rice - from some provinces in Indonesia. These products are taken from the market as samples for this analysis and they were not washed before the test. The test for pesticide residues uses two kinds of tests, which are: Rapid Test Kit that gives the qualitative result (presence or absence of active ingredients residual) without showing the amount of pesticide residue itself; and laboratory test that gives a quantitative result of pesticide active ingredients residual. Lab test data analysis shows that 98.58% of total samples from 26 provinces do not contain or have residues under MRLs so that it is stated as achieving food safety requirements. The pesticide residues include Organophosphate, Carbamate, Pyrethroid, Organochlorine, N-Phenylpyrazole, and Neonicotinoid groups of pesticide. Considering the effect of pesticide (residue) on human health and to environmental sustainability, efforts to control pesticide use need to be continued.